A techno-economic evaluation and SWOT analysis of various hydrogen energy carriers: Production to distribution - Laveet Kumar (11460088) (2025)
The transition from fossil fuel dependency to low-carbon pathways is dependent on efficient energy transportation methods. Hydrogen (H2) stands as a key player in achieving carbon-neutral targets by 2050. However, large-scale H2 transport presents technological and economic challenges. This study provides a techno-economic evaluation (TEE) and SWOT analysis of hydrogen energy carriers (HECs) for export from natural gas-rich countries, comparing four different pathways: liquid hydrogen (LH2), ammonia (NH3), methanol (MeOH), and dimethyl ether (DME). NH3 emerges as the most cost-effective option, with the lowest specific energy consumption (SEC) of 7.67 kWh/kg-H2 and a levelized cost of hydrogen (LCOH) at US$4.76/kg-H2. SWOT analysis reveals strong infrastructure and regulatory support for NH3, while LH2 is ranked higher on specific factors. Although NH3 faces safety challenges, it remains favorable for sustainable transportation. However, significant research is needed to ensure the technological and economic feasibility of these pathways for large-scale implementation. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.03.125